2022
DOI: 10.1007/s40261-022-01140-y
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Studies of Defibrotide Prophylaxis for Veno-Occlusive Disease/Sinusoidal Obstruction Syndrome

Abstract: Background and Objectives Defibrotide is approved to treat severe veno-occlusive disease/sinusoidal obstruction syndrome (VOD/SOS) after haematopoietic cell transplantation in patients aged > 1 month in the European Union and for VOD/SOS with renal/pulmonary dysfunction post-haematopoietic cell transplantation in the United States. This meta-analysis estimated the incidence and risk of VOD/SOS after intravenous defibrotide prophylaxis using the published literature. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…These patients had multiple risk factors that increased the odds of developing VOD/SOS, thereby necessitating prophylaxis with defibrotide. That said, in a separate meta-analysis of more than 3000 patients, the risk ratio for developing VOD/SOS with defibrotide prophylaxis versus control was 0.30 (95% CI: 0.12, 0.71; nominal P = 0.006) [ 22 ]. Moreover, results from a phase 3, prospective, randomised controlled study in high-risk paediatric patients demonstrated a 12% incidence of VOD/SOS by Day 30 post-HCT with defibrotide prophylaxis, while an incidence of 20% was observed in the no defibrotide control group [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients had multiple risk factors that increased the odds of developing VOD/SOS, thereby necessitating prophylaxis with defibrotide. That said, in a separate meta-analysis of more than 3000 patients, the risk ratio for developing VOD/SOS with defibrotide prophylaxis versus control was 0.30 (95% CI: 0.12, 0.71; nominal P = 0.006) [ 22 ]. Moreover, results from a phase 3, prospective, randomised controlled study in high-risk paediatric patients demonstrated a 12% incidence of VOD/SOS by Day 30 post-HCT with defibrotide prophylaxis, while an incidence of 20% was observed in the no defibrotide control group [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In total, 134/247 (54%) patients received 25 mg/kg/day of defibrotide, consistent with the dose recommended in the label; the median (IQR) dose was 25 (25,25) mg/kg/day. The median (IQR) treatment duration was 18 (11,22) days in patients with severe and 16 (8,22) days in those with very severe VOD/SOS post-HCT.…”
Section: Patient Demographics and Clinical Characteristicsmentioning
confidence: 99%
“…In terms of prophylaxis, ursodeoxycholic acid (UDA) has been associated with a significant reduction of SOS/VOD incidence in various randomized studies [75][76][77]. The use of DF as a prophylactic agent has also been shown to reduce the incidence of VOD/SOS in high-risk patients by several studies [78], whereas a systematic review by Zhang et al confirmed the lower relative risk of SOS/VOD with DF prophylaxis (risk ratio 0.47, 95% CI) [79]. A more recent meta-analysis by Cobacioglu et al confirmed a low incidence of SOS/VOD following IV DF prophylaxis regardless of age group, supporting the use of DF in the prevention of SOS/VOD [78].…”
Section: Sinusoidal Obstructive Syndrome (Sos)/veno-occlusive Disease...mentioning
confidence: 99%
“…The use of DF as a prophylactic agent has also been shown to reduce the incidence of VOD/SOS in high-risk patients by several studies [78], whereas a systematic review by Zhang et al confirmed the lower relative risk of SOS/VOD with DF prophylaxis (risk ratio 0.47, 95% CI) [79]. A more recent meta-analysis by Cobacioglu et al confirmed a low incidence of SOS/VOD following IV DF prophylaxis regardless of age group, supporting the use of DF in the prevention of SOS/VOD [78]. However, a prospective phase III study of DF prophylaxis for SOS/VOD (NCT02851407) stopped enrolment after meeting the criteria for futility although analyses are ongoing and are awaited with great interest.…”
Section: Sinusoidal Obstructive Syndrome (Sos)/veno-occlusive Disease...mentioning
confidence: 99%
“…However, all these findings are late events in the pathology of the disease [18] and emerge after histological damage is established [19]. Prophylaxis and treatment with defibrotide (Jazz Pharmaceutical, Palo Alto, CA) have shown the most promising results in several clinical trial [20][21][22][23]. Nevertheless, treatment with defibrotide can carry significant risks, such as severe hemorrhage, especially in the context of severe thrombocytopenia present in this patient population [24][25][26].…”
Section: Introductionmentioning
confidence: 99%